Highly sensitive electrochemiluminescence detection of a prostate cancer biomarker. Issue 32 (28th July 2017) - Juzgado, A.; Soldà, A.; Ostric, A.; Criado, A.; Valenti, G.; Rapino, S.; Conti, G.; Fracasso, G.; Paolucci, F.; Prato, M.
Abstract : A novel electrochemiluminescence immunosensor based on carbon nanotubes for PSMA detection in very complex matrixes exceeds the state of-the-art. Abstract : Prostate-specific membrane antigen (PSMA), a glycoprotein expressed in the prostatic epithelium endowed with enzymatic activity, is a very promising diagnostic marker for the early detection of prostate cancer. In this study, we report a novel electrochemiluminescence ELISA-like immunosensor based on carbon nanotubes and a highly specific sandwich immunoassay for the PSMA detection. To fabricate the device, an optically transparent electrode was modified with doubly functionalized multi-walled carbon nanotubes carrying amine groups and a monoclonal anti-PSMA antibody. Subsequently, to complete the sandwich immunosensing device, a second specific monoclonal anti-PSMA antibody was labelled with a electrochemiluminescent probe. Under optimized experimental conditions, the proposed sensing device exhibits a performance exceeding that of the state of-the-art in terms of the limit of detection (LOD) and limit of quantification (LOQ) as good as 0.88 ng mL −1 and 2.60 ng mL −1, respectively, in real complex samples such as cell lysates. In addition, the unique role of carbon nanotubes is also discussed by comparison with an analogue sensor assembled without the nanocarbon-based material.